The Experienced of Nurses and Family Caregivers towards Family Center Care among Hospitalize Children - Supriatin , Eva; Pangestu , Joshua (KnE Life Sciences, 2019)
Background: Family Center Care (FCC) is an approach to nursing care based on a mutually beneﬁcial partnership between the patient and family. Objective: This study aimed to describe the experience of the nurse and the family in nursing care support: Family-Centered Care in hospitalized children. Method: This research was a qualitative descriptive-analytic study, with key informants and snowball sampling techniques through inclusion obtained research subjects 3 nurses and 3 families, data analysis techniques using an interactive model that includes reduction, data display and conclusions ketch. Results: the result of this study showed six themes, namely: determinants of family support,efforts of nurses to achieve treatment goals, supporting factors for family involvement,family experience in the hospital,family dependence and family trust. In family-centered patient care, patients and families determine how they willparticipateincareanddecisionmaking.FCCasastandardofpracticecanproduce high-quality services. The FCC provides care based on mutual trust, collaboration or partnerships that work together with families by paying attention to aspects (bio, psycho, socio, and spiritual) respecting diversity and recognizing the family is a source in children’s lives. Conclusion: Provides an illustration that the themes in the research results prove family-centered care is realized through mutually beneﬁcial cooperation through partnerships between nurses and patients.